2006
DOI: 10.4141/s05-002
|View full text |Cite
|
Sign up to set email alerts
|

Using pH-dependent CEC to determine lime requirement

Abstract: Lemire, E., Taillon, K. M. and Hendershot, W. H. 2006. Using pH-dependent CEC to determine lime requirement. Can. J. Soil Sci. 86: 133-139. Controlling soil pH is important to ensure good crop yield. This study was conducted to determine whether the accuracy of the existing Shoemaker-McLean-Pratt (SMP) pH-buffer method could be improved by using the pH-dependent cation exchange capacity curve (CECpd). Soil pH, SMP and CECpd measurements were performed on 18 acid surface horizon soil samples, with textures from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The level of correlation between a LRE using these properties is similar to that provided by the Woodruff buffer and the Sikora buffer using the WI calibration (Table 4). In some regions, using alternatives to buffer methods, base saturation (Cantarella et al., 1998), soil texture (Miller & Dellavalle, 2005), or CEC (Lemire et al., 2006) to determine LREs is common practice. The relationship between OM and soil buffering capacity is well established (Brady & Weil, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of correlation between a LRE using these properties is similar to that provided by the Woodruff buffer and the Sikora buffer using the WI calibration (Table 4). In some regions, using alternatives to buffer methods, base saturation (Cantarella et al., 1998), soil texture (Miller & Dellavalle, 2005), or CEC (Lemire et al., 2006) to determine LREs is common practice. The relationship between OM and soil buffering capacity is well established (Brady & Weil, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in several states, including New York, Missouri, Wisconsin, and Kansas, found that these “green” buffer options successfully replace historically used buffer methods containing hazardous materials (Dietzel et al., 2009; Godsey, Pierzynski, Mengel, & Lamond, 2007; Laboski & Peters, 2005; Nathan et al., 2012). Soil properties such as BS (Cantarella et al., 1998), cation exchange capacity (CEC) (Lemire, Taillon, & Hendershot, 2006), and soil texture represented by the saturated paste test (Miller & Dellavalle, 2005) have also been used for LREs. Using these characteristics instead of a buffer reduces hazardous waste production and labor while providing alternative and potentially more effective strategies for deriving LREs than traditional buffer methods.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Edmeades (1982) reported that effective cation exchange capacity (ECEC) increased with increasing soil pH. Lemire et al (2006) reported that CEC increased as a direct function of the amount of lime added, if the final pH of the solution remained below 7. They further reported that a 1 cmol (+) kg -1 increase in CEC for every 2.1 t ha -1 of limestone added to all soils regardless of texture, organic matter or other soil properties.…”
Section: Effect Of Limestone On Soil Properties At 0-15 CM and 15-30 Cmmentioning
confidence: 94%
“…For example, soil pH was used in all four studies, SOM was used in three cases (Keeney & Corey, 1963;Lemire et al, 2005;McFarland et al, 2020), and KCl-extractable Al was used in two studies (McFarland et al, 2020;Miller et al, 2005). Overall, the four soil property models developed by Keeney and Corey (1963), Lemire et al (2005), and McFarland et al (2020 were shown to be acceptably accurate for estimating LR in their respective regions, based on r 2 values ranging from .71 to .88. However, each model had slightly lower r 2 values than at least one buffer method evaluated in the same study, indicating that, in general, buffer methods were more accurate for estimating lime requirement than methods based on multiple soil test properties (Keeney & Corey, 1963;Lemire et al, 2005;McFarland et al, 2020;Miller et al, 2005).…”
Section: Core Ideasmentioning
confidence: 99%